Investigation on the dissociation flow of methane hydrate cores: Numerical modeling and experimental verification. (18th May 2017) - Chen, Lin; Yamada, Hikaru; Kanda, Yuki; Okajima, Junnosuke; Komiya, Atsuki; Maruyama, Shigenao
Graphical abstract: Highlights: Experiment on methane hydrate core is set-up and verified with numerical models. Dissociation characteristics of both non-porous core and porous core are compared. Heat transfer/permeability are critical for production enhancement. Scaling up from core to reservoir scale and challenges are discussed. Abstract: Methane hydrate has become one of the important topics in recent years as there are more and more reports on possible actual production systems. The most challenging problem for stable methane hydrate production from sea beds or under permafrost regions lies in the complex flow and transportation process, which usually occurs inside the unconsolidated porous layers. The current study is focused on laboratory-scale explorations of the basic dissociation behaviors of methane hydrate. A high-pressure experimental system for the methane hydrate synthesis and dissociation process has been established in this study. The experimental system is specially designed to form and store the methane hydrate under high pressure and low temperature conditions. The mixing of sand with the formed methane hydrate makes it possible to control the initial saturation for dissociation in the current study. A numerical simulation model for core-scale dissociation flow has also been set up, and good agreement with the experimental data was found. It is found that the dissociation on a core scale is more heat-transfer controlled. Through comparisons with previous experimental and numerical results, it is known that the operation strategy will significantly affect the dissociation parameter behaviors. The effects of the initial temperature and permeability on the dissociation process are also shown in this study. Future considerations of core-scale models and reservoir-scale production strategies are also discussed in detail.